The mobile money's poverty-reducing promise: Evidence from Cambodia. (June 2021) - Seng, Kimty
Highlights: Mobile money increases household income per capita. Mobile money increases the likelihood that households receive domestic remittances. The effects are greater if the mobile money users are headed by financially-literate persons. Abstract: Fin-tech platforms such as mobile money services are likely to have a potential to promote socio-economic development in the developing world. Recently, the arguments about the poverty-alleviating promise of mobile money have been controversial and inconclusive. This article analyses the effects of mobile money on household poverty in terms of household income per capita in Cambodia by using an endogenous switching model with data from the Cambodia FinScope Consumer Survey conducted in 2015. A complementary analysis of the effects on domestic remittances is performed to give more insights into the potential effects by adopting an endogenous switching probit model. The results suggest that households taking up mobile money services are likely to enjoy higher household income per capita, with the complementary results illustrating that the uptake of mobile money services is likely to increase the likelihood that households receive domestic remittances. Accounting for financial literacy through its interaction with the uptake of mobile money services, the results reveal that the effects are likely greater if the household users are headed by financially-literate persons.